MULTIVARIATE STATISTICAL APPROACH FOR ASSESSMENT OF GROUNDWATER QUALITY AT HADEJIA-JAMAARE-KOMADUGU- YOBE BASIN, NIGERIA - A. G, TAHIR; M. L, GARBA; A, MUSTAPHA; A.N, AHMAD, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
Assessment of the processes that control groundwater quality is significant for the sustainable development of water resources. Groundwater samples collected from the study area were appropriately analyzed in the laboratory. The study approach employed the use of multivariate statistical tools; Principal component and cluster analyses on the data, in order to understand the groundwater condition of the area, with a view to the concentration of different parameters in the water and other factors controlling the groundwater quality. Based on the Eigen value-one criterion, eleven (11) components were chosen after Varimax rotation. The first Varimax factor (VF1) contained strong factor loadings on Pb, Mo, Cd and Ni which account for 15.404% variance of the water quality data. The 2nd Varimax factor (VF2) has strong loadings on Electrical conductivity (EC), total dissolved solid (TDS), Cl and Temperature, with a variance of 14.068%. The 11 Varimax factors explained 81.91% of the variability of the water quality data. The strong loading for Pb, Mo and Cd could be due to industrial effluents. While the high loading for EC, TDS and Cl could be due to salinity build up in the area as a result of the intensive agricultural activities. These results suggest the possibility of effects of anthropogenic activities; industrial effluents and intensive application of agro-chemicals. There is need for proper discharge of industrial effluents and application of agro-chemicals.